2017
DOI: 10.1155/2017/1875872
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Soft Texture Fish Fillets through Brine Injection Technology

Abstract: An exploratory study was conducted to determine if multineedle injection technology could deliver protease inhibitor ingredients into fish fillets at sufficient levels to inhibit protease activity. Pacific whiting is used as a model in this study. Fillet treatments ( = 8/treatment) included noninjection (C), injection of base brine containing 3% salt and 3% sodium tripolyphosphate (B), injection of base brine and 3% egg white (B EW ), and injection of base brine, 0.1% xanthan gum, and 3% dried potato extract (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In this study, the sample was thawed before measured the hardness so, when structure damaged by freezing, the structure was softer. The softer of catfish fillet was also reported by (Harikedua & Mireles DeWitt, 2017). The changes in catfish ( Silurus glanis Linne) muscle as by different freeze–thaw cycles was also reported (Benjakul & Bauer, 2001).…”
Section: Resultssupporting
confidence: 74%
“…In this study, the sample was thawed before measured the hardness so, when structure damaged by freezing, the structure was softer. The softer of catfish fillet was also reported by (Harikedua & Mireles DeWitt, 2017). The changes in catfish ( Silurus glanis Linne) muscle as by different freeze–thaw cycles was also reported (Benjakul & Bauer, 2001).…”
Section: Resultssupporting
confidence: 74%
“…The level of NaCl and STPP selected for brines in this study was based on previous studies (Almli & Hersleth, ; Bigelow & Lee, ; Harikedua & Mireles DeWitt, ) and recommendations from the phosphate supplier. Ten treatments were evaluated (Table ): (1) no injection (NI), (2) injection of water (W), (3) injection of base brine containing 3% salt and 3% STPP (B), (4) injection of base brine coupled with 1% EW (B 1EW ), (5) injection of base brine plus 2% EW (B 2EW ), (6) injection of base brine and 3% EW (B 3EW ), (7) injection of base brine combined with the addition of 0.1% XG as a suspension aid (B XG ), (8) injection of base brine, 0.1% XG, and 1% PE (B 1PE ), (9) injection of base brine, 0.1% XG, and 2% PE (B 2PE ), and (10) injection of base brine, 0.1% XG, and 3% PE (B 3PE ).…”
Section: Methodsmentioning
confidence: 99%
“…Xanthan gum was selected due to its rapid solubility in a cold salt/phosphate brine and it was determined a minimum of 0.1% was required to achieve suspension of B PE up to 3% w/w. Initial studies were subsequently designed to determine whether 3% B EW or 3% B PE could be sufficiently distributed by injection into a fillet to inhibit protease activity (Harikedua & Mireles DeWitt, ). Results demonstrated that both B PE and B EW inhibited protease activity in the raw fillet.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the interest in brine's ability to improve the quality of whole muscle beef, pork and poultry products is increasing (Harikedua & Mireles DeWitt, 2017). During the salt treatment, a thin layer of denaturated proteins is obtained on the surface of the fillet, which protects it from the external factors, reduces drying during freezing and weight loss during defrosting (Valtýsdóttir et al, 2010(Valtýsdóttir et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%